Peran Kompetensi Kepala Sekolah dalam Upaya Meningkatkan Mutu Pendidikan di SMAN 1 Pacet Mojokerto - Andi Herlina (Jurnal Pustaka Cendekia Pendidikan, 2026)
Improving the quality of education is a top priority in the management of educational institutions, which is greatly influenced by the role of the principal as an educational leader. The principal does not only serve as an administrator, but also as a transformational leader who has the ability to direct, motivate, and manage all components of the school to work synergistically in achieving educational goals. At SMAN 1 Pacet Mojokerto, the role of the principal is very important in encouraging the creation of a conducive, innovative, and achievement-oriented learning environment. This study aims to analyze (1) The role of the principal's competence in efforts to improve the quality of education at SMAN 1 Pacet Mojokerto, (2) Implications of the role of the principal's competence in efforts to improve the quality of education at SMAN 1 Pacet Mojokerto. This study uses a qualitative research type using a descriptive form. The object of the study is SMAN 1 Pacet Mojokerto. The results of this study indicate that the principal has a strategic role in creating a conducive educational environment, improving the performance of teachers and education personnel, and building a superior school culture. (1) The role of the principal's competence in efforts to improve the quality of education at SMAN 1 Pacet Mojokerto has three important roles that are interrelated, namely personality competence, managerial competence and entrepreneurial competence. The quality of education at SMAN 1 Pacet Mojokerto includes content standards, process standards and graduate competency standards. (2) The implications of the role of the principal's competence in efforts to improve the quality of education at SMAN 1 Pacet Mojokerto, namely having a significant impact on improving the quality of education, influencing the implementation of the curriculum systematically and in a directed manner and encouraging innovation in program management and developing student potential.